Odpowiedź :
Odpowiedź:
1.
a)
5 * 5 * 5 = 5³
b)
0,2 * 0,2 * 0,2 * 0,2 = 0,2^4
c)
(-1) * (-1) * (-1) * (-1) = (-1)^4
d)
2/7 * 2/7 * 2/7 * 2/7 * 2/7 = (2/7)^5
2.
a)
3³ = 27
b)
1^200 = 1
c)
(-1)^5 = -1
d)
(2/5)² = 4/25
e)
1,1^4 = 1,4641
f)
(-10)^0 = 1
g)
(2 2/3)³ = (8/3)³ = 512/27 = 18 26/27
h)
(-0,2)³ = -0,008
i)
(-4)³ = -64
j)
(-1 2/7)² = (-16/7)² = 256/49 = 5 11/49
3.
a)
(-6)^8 = 6^8
b)
-(-5)^9 > -5^9
c)
(-3)^11 < (-3)^10
d)
-(-12)^13 < (-12)^14
e)
(1/4)³ < 4³
f)
(1/3)^6 < (1/3)^5
g)
(1/5)^9 < (-1/5)^4
h)
(1/7)^5 > (-1/7)^6
4.
a)
(-3)^4 - (-3)³ * 3 = 64 + 27 * 3 = 64 + 81 = 145
b)
5^0 * 7 - 18 * (1/3)² = 7 - 18 * 1/9 = 7 - 2 = 5
c)
(3/5)² - 3²/5 + 3/5² = 9/25 - 9/5 + 3/25 = 12/25 - 1 4/5 = 12/25 - 1 20/25 =
= -1 8/25
Szczegółowe wyjaśnienie: